The cadastre with respect to the Integrated System of Real Estate Information - Konieczna, Jadwiga (International Conference “Environmental Engineering”, 2017)
The strength of each country is determined by two factors, namely the economy and efficient administration. One of the instruments allowing the administration to perform its tasks is a fully operational system of real estate information, which meets the requirements commonly imposed on the systems of spatial information. This includes such prerequisites as: the reliability of up-to-date information issued from the system, easy access to this information, and ensuring the protection thereof. An effective real estate management system is largely determined by an efficiently operating Cadastre, an institution with a century-old tradition, to which the legislator has assigned specific tasks, and which provides the basis for specific decision-making actions associated, inter alia, with the real estate market. The aim of the paper is to present the scope of work carried out in Poland as part of the development of the Integrated System of Real Estate Information (Polish: Zintegrowany System Informacji o Nieruchomościach, ZSIN), and the possibilities for the use of existing information systems with a particular emphasis on cadastral data. The paper defines the tasks, principles and functions of the Cadastre, as well as the indicated direction of changes allowing the Cadastre to be adjusted to the proper operation of the ZSIN.